MENINGKATKAN PARTISIPASI MASYARAKAT MELALUI PEMBANGUNAN INFRASTRUKTUR DI DESA SUKATANI KECAMATAN NGAMPRAH KABUPATEN BANDUNG BARAT - desi arisanti gustiyani (IKIP Siliwangi, 2019)
Community participation in development policies in countries that implement democracy including in Indonesia is not new. Community participation is a technical process to provide wider opportunities and authority to the community together to solve various problems. As a concept and practice of development, the concept of participation was only discussed in the 60s when various international institutions promoted participation in development planning, implementation and evaluation practices. The importance of the community in village development is to remember the local community who are more aware of various problems such as the construction of village infrastructure and facilities, the development of local economic potential, and the utilization of existing natural and environmental resources so as to facilitate the development planning and implementation process. The purpose of this study: To describe the condition of the community of Sukatani village, to determine community participation in infrastructure development, to determine efforts to increase community participation and to find out the supporting and inhibiting factors in efforts to increase participation. The research method used in this study is adapted to the objectives of the researcher, so this research method uses a qualitative descriptive method. The results of the pre-survey research showed that the issue of public participation in the development process was not as expected and there were still problems with community participation in development in Sukatani Village. The conclusion of the explanation above is that community participation in Sukatani Village is still relatively low. It needs an increase in the awareness and concern of the local community that it is important to participate in maintaining, caring for, and maintaining every outcome of village development that has been carried out.